Letter (copy) : Photograph - Tewson, Vincent
021-0061-001 HVT/EAB/AC/617 International 14th April, 1937. Mr. Jean Longuet, Conseil Général de la Seine, PARIS. Dear Comrade Longuet, PHOTOGRAPH. With reference to your letter of 10th April, I have pleasure in returning herewith your photograph as you request. I may say that our reason for requesting the I.F.T.U. to approach you for the loan of this photograph was that we were considering the issue of a souvenir programme in connection with the Kingsway Hall meeting, a project which we had to abandon for lack of time to produce a suitable piece of work worthy of the occasion. Yours sincerely, Assistant Secretary. Photograph. 292/946/21/61